Archeology - Foiles , Stacey; Naughton Tom.; Valcour , Nicolas (USA : Discovery Channel, 1998)
If you are real archaeologist and scholar, I could see getting upset with Mr. J., the "naked archaeologist." To me (not one), he is just a showboat. Calling it "Naked" means pandering to get attention. Getting himself "crucified " is a good example. I could not watch that show. But I could not watch Mel Gibson's movie about that topic either. But on the positive side, the locales they visit are real. And he does engage real people in the field who argue all the time with each other anyway. I like any approach to civil discussion about ancient times that doesn't get all misty and religious and doctrinaire. So the show is usually quite fun to watch despite the obvious ego bumping. I give the show a solid "B" and look forward to next week.